Ésteres sintéticos derivados do ácido 3-metil-4-nitrobenzoico e avaliação da sua atividade antifúngica - Ferreira, Alana Rodrigues (2018)
The 3-methyl-4-nitrobenzoic acid is a compound obtained through synthetic processes, low cost and used in several studies as a precursor in the production of bioactive molecules. The present dissertation involved the preparation, purification and structural characterization of eleven esters derived from 3-methyl-4-nitrobenzoic acid in order to evaluate them for their antifungal capacity against yeast species of the genus Candida: C. albicans, C. glabrata, C. krusei and C. guilliermondii, opportunistic pathogens of clinical importance that, with the increase of the use of the antifungal agents, have been developing mechanisms of resistance to the currently available drugs; which represents an extreme difficulty for the treatment of infections caused by these microorganisms. Four different methodologies were used for the esterifications: Fischer esterification, esterification with alkyl and aryl halides, Mitsunobu reaction and Steglich reaction; the yields of the esters obtained ranged from 12% to 83%. In the antifungal tests, the minimum inhibitory concentration (MIC) was determined with the 96-well plate microdilution technique and subsequent determination of the minimum fungicidal concentration (CFM) in solid culture medium. With the evaluation of the antifungal capacity of the prepared esters, it was possible to observe that all were bioactive against at least one of the tested strains and presented fungicidal activity. The best results were related to the strain of C. guilliermondi 207, in which, AR1 presented inhibitory activity at the concentration of 0.039 μmol/mL and AR6 at 0.031 μmol/mL. Regarding the structural characteristics of the esters that influence the antifungal bioactivity, the importance of the side alkyl chains was found. It was also observed that the insertion of a terpenic substructure or aromatic groups, in most cases, were not relevant for the optimization of the bioactivity or contributed to the ester inactivity.